Transplante hepático pediátrico: experiência do Hospital das Clínicas da UFMG - Marta Celeste de Oliveira Mesquita (2007)
Objectives: To evaluate the experience of the division of liver transplantation of the Alfa Institute of HC/UFMG, over the first ten years.Method: Descriptive study, through retrospective analysis of 84 children and adolescents enrolled in liver transplantation waiting list of HC/UFMG, from March 1995 to January 2006, by the following facts: age, sex, blood group, aetiology of underlying liver disease, Child-Pugh, Malatack, model for end-stage liver disease (MELD) and pediatric end-stage liver disease (PELD) scores, time in waiting list, complications and survival after the procedure. Results: Since 1995, 40 children have had 42 liver transplants. Twenty six died in the waiting list. Biliary atresia was the most frequent indication for transplant. The median age was 6,6 years (range 1,9 to 19,8 years). Post liver transplant mortality was 32,5% (13 of 40 children). Survival after 6 months and 5 years post-transplant was 70% and 67,2%, respectively. The time of waiting in the liver transplant list presented medium of 291 days. Complications unrelated to graft had occurred in 17 of the 42 transplants (40,5%), including instabilityhemodinamic (40,5%) and neurological complications (38%). Complications related to graft had occurred in 24 of 42 transplants (57,1%), including vascular complications (30,8%), with the hepatic artery thrombosis being the most frequent (16,6%); acute rejection had occurred in 19%. The most frequent cause of mortality was primary non-function (30,7%). Conclusion: The joined results in our service are similar to what was observed in literature, about the indications and complications post-transplant, what emphasizes the importance of work carried through until then. However, we still have the possibility and necessity of improvement, with the objective to reduce complications unrelated to graft and vascular complications, especially thoserelated to hepatic artery, so that an improvement of survival might occurs in the long term.